Design of a MOF based on octa-nuclear zinc clusters realizing both thermal stability and structural flexibility. Issue 8 (4th January 2022) - Ma, Yunsheng; Tang, Xiaoyan; Chen, Ming; Mishima, Akio; Li, Liangchun; Hori, Akihiro; Wu, Xiaoyu; Ding, Lifeng; Kusaka, Shinpei; Matsuda, Ryotaro
Abstract : We demonstrate the generation of a MOF (Zn8 - as ) based on octa-nuclear zinc clusters from a curved ligand and Zn(ii ) in DMF and H2 O. Zn8 - de displays gated adsorption for C2 H2 and type-I adsorption for CO2, attributed to the framework flexibility. Abstract : An octa-nuclear zinc (Zn8 ) cluster-based two-fold interpenetrated metal–organic framework (MOF) of [(CH3 )2 NH2 ]2 [Zn8 O3 (FDC)6 ]·7DMF (denoted as Zn8 - as ; H2 FDC = 9 H -fluorene-2, 7-dicarboxylic acid; DMF = N, N -dimethylformamide) was synthesized by the reaction of a hard base of a curved dicarboxylate ligand (H2 FDC) with the borderline acid of Zn(ii ) under solvothermal conditions. Zn8 - as shows significant crystal volume shrinkage upon heating, yielding a solvate-free framework of [(CH3 )2 NH2 ]2 [Zn8 O3 (FDC)6 ] (Zn8 - de ). Zn8 - de displays gated adsorption for C2 H2 and type-I adsorption for CO2, attributed to the framework flexibility and the different interactions between the gas molecules and the host framework.